Computational Fractional Flow Reserve From Coronary Computed Tomography Angiography—Optical Coherence Tomography Fusion Images in Assessing Functionally Significant Coronary Stenosis - Lee, Yong-Joon; Kim, Young Woo; Ha, Jinyong; Kim, Minug; Guagliumi, Giulio; Granada, Juan F.; Lee, Seul-Gee; Lee, Jung-Jae; Cho, Yun-Kyeong; Yoon, Hyuck Jun; Lee, Jung Hee; Kim, Ung; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Coronary computed tomography angiography (CTA) and optical coherence tomography (OCT) provide additional functional information beyond the anatomy by applying computational fluid dynamics (CFD). This study sought to evaluate a novel approach for estimating computational fractional flow reserve (FFR) from coronary CTA-OCT fusion images. Methods: Among patients who underwent coronary CTA, 148 patients who underwent both pressure wire-based FFR measurement and OCT during angiography to evaluate intermediate stenosis in the left anterior descending artery were included from the prospective registry. Coronary CTA-OCT fusion images were created, and CFD was applied to estimate computational FFR. Based on pressure wire-based FFR as a reference, the diagnostic performance of Fusion-FFR was compared with that of CT-FFR and OCT-FFR. Results: Fusion-FFR was strongly correlated with FFR (r=0.836, P<0.001). Correlation between FFR and Fusion-FFR was stronger than that between FFR and CT-FFR (r=0.682, P<0.001; z statistic, 5.42, P<0.001) and between FFR and OCT-FFR (r=0.705, P<0.001; z statistic, 4.38, P<0.001). Area under the receiver operating characteristics curve to assess functionally significant stenosis was higher for Fusion-FFR than for CT-FFR (0.90 vs. 0.83, P=0.024) and OCT-FFR (0.90 vs. 0.83, P=0.043). Fusion-FFR exhibited 84.5% accuracy, 84.6% sensitivity, 84.3% specificity, 80.9% positive predictive value, and 87.5% negative predictive value. Especially accuracy, specificity, and positive predictive value were superior for Fusion-FFR than for CT-FFR (73.0%, P=0.007; 61.4%, P<0.001; 64.0%, P<0.001) and OCT-FFR (75.7%, P=0.021; 73.5%, P=0.020; 69.9%, P=0.012). Conclusions: CFD-based computational FFR from coronary CTA-OCT fusion images provided more accurate functional information than coronary CTA or OCT alone.